ANALYSIS OF FACTORS AFFECTING RICE PRICES IN NORTH SUMATRA PROVINCE - Faisal Azhari Baldan Panjaitan; Satrio Joko Wibowo; Aadil Hussain Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the factors influencing rice prices in North Sumatra Province and identify the most dominant variables. The data used are secondary time series data for the period 2012–2024, analyzed using the multiple linear regression method with the Ordinary Least Square (OLS) approach. The results show that rice prices in supplying areas, rice consumption, and population significantly influence rice prices in North Sumatra, while the price of dry harvested grain does not. The coefficient of determination value of 93.4% indicates that the model is able to explain most of the variation in rice prices. Rice consumption is the most dominant variable in influencing rice prices.